2009
DOI: 10.1002/14651858.cd007483.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin-based combination therapy for treating uncomplicated malaria

Abstract: Dihydroartemisinin-piperaquine is another effective first-line treatment for P. falciparum malaria.The performance of the non-ACT (amodiaquine plus sulfadoxine-pyrimethamine) falls below WHO recommendations for first-line therapy in parts of Africa.In areas where primaquine is not being used for radical cure of P. vivax, ACTs with long half-lives may provide some benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
199
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 231 publications
(210 citation statements)
references
References 93 publications
4
199
1
2
Order By: Relevance
“…In this way, even in areas with chloroquine resistance, the antimalarial effects of both drugs and the possibly beneficial immune-modulating effects of chloroquine could be combined. Another interesting candidate might be dihydroartemisinin-piperaquine, which is an effective first-line treatment for P. falciparum malaria in both adults and children (Four Artemisinin-Based Combinations (4ABC) Study Group, 2011;Sinclair et al, 2009). …”
Section: Innovative Application Of Drug Use In the Fieldmentioning
confidence: 99%
“…In this way, even in areas with chloroquine resistance, the antimalarial effects of both drugs and the possibly beneficial immune-modulating effects of chloroquine could be combined. Another interesting candidate might be dihydroartemisinin-piperaquine, which is an effective first-line treatment for P. falciparum malaria in both adults and children (Four Artemisinin-Based Combinations (4ABC) Study Group, 2011;Sinclair et al, 2009). …”
Section: Innovative Application Of Drug Use In the Fieldmentioning
confidence: 99%
“…A Cochrane meta-analysis of 50 studies 23 and a meta-analysis including 8 studies in Africa 24 concluded that there is enough evidence to suggest that AL more effectively increases crude ACPR rates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review comparing artesunate plus amodiaquone, artemeter-lumefantrine, artesunate plus sulfadoxinepyrimethamine, amodiaquone plus sulfadoxinepyrimethamine and dihydroartemisinin-piperaquine for treating uncomplicated P. falciparum infection has shown that all ACTs achieved the World Health Organization (WHO) defined threshold of efficacy [11]. ACTs were superior to amodiaquine plus sulfadoxine-pyrimethamine in East Africa.…”
Section: Artemisinin Combination Therapies (Acts)mentioning
confidence: 99%